Could Total Colectomy with Ileorectal Anastomosis Be an Alternative to Total Proctocolectomy with Ileal Pouch-Anal Anastomosis in Selected Ulcerative Colitis Patients? - Francesco Tonelli; Carmela Di Martino; Francesco Giudici (Gastroenterology Research and Practice)
Purpose. To evaluate ileorectal anastomosis (IRA) in selected ulcerative colitis patients. Methods. Early and late complications after IRA and IPAA were investigated. Bowel function and quality of life were assessed. Functional and QoL studies were performed as a matched pair analysis, comparing 98 patients who underwent IRA versus 98 patients who underwent IPAA. Results. In IRA group, 2 patients (1.6%) developed anastomotic l dysplasia (HGD) developed in 3 patients dysplasia (HGD) developed in 3 patients eakage, 1 patient (0.8%) had intestinal obstruction, and 2 patients (1.6%) had abdominal hematoma. Mean follow-up was 11.5 (range: 2–24.3) years. Failure of IRA occurred in 19 patients (15.1%); in 12 patients (9.5%), failure was related to severe proctitis, in 3 patients (2.4%), it was related to the development of high-grade dysplasia, and in 4 patients (3.2%), it was related to the development of rectal cancer. About functional results, stool consistency [liquid (6.7% of IRA patients versus 29% of IPAA patients; p=0.003)], daily soiling (0% versus 6%; p=0.01), and nocturnal soiling (6% versus 25.5%; p=0.03) were statistically different. Only 1% of IRA patients versus 11% of IPAA patients had episodes of perianal inflammation (p=0.007). CGQoL was 0.72 (±0.14, SD) in IRA patients and 0.75 (±0.11, SD) in IPAA patients (p=ns). Conclusion. In selected patients, IRA is an appropriate surgical option, with low morbidity, comparable quality of life, and better functional results than IPAA.